Testing for sexually transmitted infections among students: a discrete choice experiment of service preferences. Issue 10 (28th October 2013) - Llewellyn, Carrie D; Sakal, Chloe; Lagarde, Mylene; Pollard, Alex; Miners, Alec H
Abstract : Objectives: To assess preferences among students for sexually transmitted infection (STI) testing services, with a view to establishing strength of preference for different service attributes. Design: Online discrete choice experiment (DCE) questionnaire. Setting: South East of England. Participants: A convenience sample of 233 students from two universities. Outcomes: Adjusted ORs in relation to service characteristics. Results: The study yielded 233 responses. Respondents' ages ranged from 16 to 34 years with a mean age of 22 years. Among this sample, the respondents demonstrated strong preferences for a testing service which provided tests for all STIs including syphilis, herpes and HIV (OR 4.1; 95% CI 3.36 to 4.90) and centres staffed by a doctor or nurse with specialist knowledge of STIs (OR 2.1; 95% CI 1.78 to 2.37). Receiving all test results, whether positive or negative, was also significantly preferable to not being notified when tests were all negative ('no news is good news'; OR 1.3; 95% CI 1.16 to 1.5). The length of time waiting for an appointment and the method by which results are received were not significant service characteristics in terms of preferences. Patient level characteristics such as age, sex and previous testing experience did not predict the likelihood of testing. Conclusions: This study demonstrates that of the examined attributes, university students expressed the strongest preference for a comprehensive testing service. The next strongest preferences were for being tested by specialist STI staff and receiving negative as well as positive test results. However, it remains unclear how strong these preferences are in relation to characteristics which were not part of the study design and whether or not they are cost-effective.